2020
DOI: 10.1002/acr2.11150
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the Zoster Vaccine Recombinant Adjuvanted in Rheumatoid Arthritis and Other Systemic Rheumatic Disease Patients: A Single Center's Experience With 400 Patients

Abstract: Objective. Patients with rheumatoid arthritis (RA) and other systemic rheumatic diseases (SRDs) are at increased risk of developing herpes zoster (HZ). Zoster recombinant adjuvanted (ZRA) is a recombinant vaccine approved by the Food and Drug Administration in 2018. Concern has been raised that the ZRA may trigger disease flares in rheumatology patients who are immunocompromised. We investigated the impact of the ZRA vaccine in patients with RA and SRD and measured the incidence of flares and side effects.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 15 publications
3
33
0
6
Order By: Relevance
“…Our data show a very low flare rate after the BNT162b2 COVID‐19 vaccine in patients with RA in remission and are consistent with previous findings about Varicella‐zoster virus (6.7%) ( 4 ) and Hepatitis B virus (2.2%) ( 5 ) vaccinations. Because remission is not commonly obtained in the real world, we are aware that our findings may not be generalizable to all patients with RA receiving COVID‐19 vaccination.…”
supporting
confidence: 92%
“…Our data show a very low flare rate after the BNT162b2 COVID‐19 vaccine in patients with RA in remission and are consistent with previous findings about Varicella‐zoster virus (6.7%) ( 4 ) and Hepatitis B virus (2.2%) ( 5 ) vaccinations. Because remission is not commonly obtained in the real world, we are aware that our findings may not be generalizable to all patients with RA receiving COVID‐19 vaccination.…”
supporting
confidence: 92%
“…The first retrospective review of 403 patients with rheumatic disease vaccinated with the RZV found a 7% incidence of disease flare within 12 weeks of receiving a vaccine dose; this incidence was considered to be similar to expected rates from clinical trials. 66 However, a second retrospective review of 359 patients with rheumatic diseases found that 16% had a flare of their disease within 12 on September 12, 2021 by guest. Protected by copyright.…”
Section: Safety In Patients With Rheumatic Diseasesmentioning
confidence: 99%
“…Common side effects are infections, including serious and opportunistic infections and herpes zoster (45)(46)(47). Vaccination with recombinant adjuvanted herpes zoster subunit is generally safe in patients with autoimmune disease, although flares are not uncommon (48,49). Investigation of the serologic response to the recombinant vaccine in RA patients treated with jakinibs suggests satisfactory antibody responses and acceptable tolerability (50).…”
Section: Safety Of Approved Jakinibsmentioning
confidence: 99%